Comida instagramável: uma análise da publicidade de alimentos da cafeteria Kalena Café no instagram sob a perspectiva dos Ecossistemas Comunicacionais - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
This dissertation investigates the phenomenon of instagramable foods and seeks to understand how they are used as a communication strategy to attract consumers and generate engagement on Instagram. The main objective is to analyze, from the perspective of communicational ecosystems, the advertising of food at the Kalena Café on Instagram; the specific objectives aim to understand the process of transforming advertising practices, thereby categorizing the contents of images and captions of publications which are considered instagramable foods on the page. We measure the amount of comments and likes generated, examining the dialogues established in the comments and, finally, we investigate the levels of engagement resulting from the brand. The research qualifies a Case Study of a quantitative and qualitative nature in which it uses a netnographic approach to analyze the one hundred and twenty-nine (129) images of instagramable foods published on the @kalenacafe profile in the period between April and October 2018. From communicational ecosystemic vision that involves the phenomenon of instagramable foods and makes it possible to understand the advertising strategies as interconnected systemic communicational objects by harboring in their communicative strategies the incorporation of consumers no longer passively, but as co-producers and articulators of the persuasive message. The results showed that the cafeteria's communicative strategy based on the advertising of the merchandise sold through images of foods with visually instagramable aesthetics, persuasive captions illustrated why consumers actively participated in the merchandise advertising process by including other followers through the interconnections established in the comments within the practice of engagement. The research pointed out that the new collaborative strategy between the brand and the followers resulted in a positive percentage of 41,37% of engagement between likes and monthly comments for the community, and that the new advertising communication strategies on social networks are not only related to the formats and languages demanded by the new technologies, but in the importance of incorporating the consumer as a co-producer, articulator and key interlocutor for the effectiveness of communication strategies.
Instagramable food: an analysis of Kalena Cafeteria food advertising coffee on instagram from the perspective of communication ecosystems
Keywords: Redes sociais on-line; Fotografia na publicidade; CIÊNCIAS SOCIAIS APLICADAS: COMUNICAÇÃO; Instagramismo; Comida Instagramável; Engajamento; Publicização; Ecossistemas Comunicacionais